Novel artificial cell microencapsulation of a complex gliclazide-deoxycholic bile acid formulation: A Characterization Study - Mooranian, Armin; Negrulj, Rebecca; Chen-Tan, Nigel; Al-Sallami, H.; Fang, Zhongxiang; Mukkur, Trilochan; Mikov, Momir; Golocorbin-Kon, S.; Fakhoury, M.; Arfuso, Frank; Al-Salami, Hani (Dove Medical Press Ltd., 2014)
Gliclazide (G) is an antidiabetic drug commonly used in type 2 diabetes. It has extrapancreatic hypoglycemic effects, which makes it a good candidate in type 1 diabetes (T1D). In previous studies, we have shown that a gliclazide-bile acid mixture exerted a hypoglycemic effect in a rat model of T1D. We have also shown that a gliclazide-deoxycholic acid (G-DCA) mixture resulted in better G permeation in vivo, but did not produce a hypoglycemic effect. In this study, we aimed to develop a novel microencapsulated formulation of G-DCA with uniform structure, which has the potential to enhance G pharmacokinetic and pharmacodynamic effects in our rat model of T1D. We also aimed to examine the effect that DCA will have when formulated with our new G microcapsules, in terms of morphology, structure, and excipients’ compatibility. Microencapsulation was carried out using the Büchi-based microencapsulating system developed in our laboratory. Using sodium alginate (SA) polymer, both formulations were prepared: G-SA (control) at a ratio of 1:30, and G-DCA-SA (test) at a ratio of 1:3:30. Complete characterization of microcapsules was carried out. The new G-DCA-SA formulation was further optimized by the addition of DCA, exhibiting pseudoplastic-thixotropic rheological characteristics. The size of microcapsules remained similar after DCA addition, and these microcapsules showed no chemical interactions between the excipients. This was supported further by the spectral and microscopy studies, suggesting microcapsule stability. The new microencapsulated formulation has good structural properties and may be useful for the oral delivery of G in T1D.